Modulation of E-Cadherin and N-Cadherin by ovarian steroids and embryonic stimuli. (December 2021) - Tiwari, Abhishek; Ashary, Nancy; Singh, Neha; Sharma, Shipra; Modi, Deepak
Graphical abstract: Highlights: Sorting of E-Cadherin in endometrial epithelium is dynamically regulated during the estrus cycle. Combined action of estrogen & progesterone leads to apico- /basolateral sorting of E-Cadherin. This sorting can be recapitulated in mice endometrium and 3Dspheroids of human endometrial epithelium. During implantation, presence of an embryo leads to loss of E-Cadherin and gain of N cadherin in the endometrial epithelium. The switch from E-Cadherin to N-Cadherin is suggestive of epithelial to mesenchymal transition. Abstract: Endometrium is a dynamic tissue that undergoes extensive remodelling to attain a receptive state which is further modulated in presence of an embryo for successful initiation of pregnancy. Cadherins are the proteins of the junctional complex of which E-cadherin (E-Cad) is crucial for maintaining epithelial cell state and integrity of the epithelial barrier; gain of N-cadherin (N-Cad) in epithelial cells leads to epithelial to mesenchymal transition (EMT). In the present study, we investigated the expression of E-Cad and N-Cad in the mouse endometrial luminal epithelium and its modulation by estrogen, progesterone, and embryonic stimuli. We observed that E-Cad is diffusely expressed in the luminal epithelium of mouse endometrium during the estrus stage and upon estrogen treatment. It is apico-laterally and basolaterally sorted at the diestrus stage and in response to the combined treatment of estrogen and progesterone. In 3D spheroids of human endometrial epithelial cells, combined treatment with estrogen and progesterone led to lateral sorting of E-Cad without any effects on its mRNA levels. at the time of embryo implantation, there is loss of E-Cad along with the gain of N-Cad and SNAIL expression suggestive of EMT in the luminal epithelium. This EMT is possibly driven by embryonic stimuli as treatment with estrogen and progesterone did not lead to the gain of N-Cad expression in the mouse endometrium in vivo or in human endometrial epithelial cells in vitro . In conclusion, the present study demonstrates that steroid hormones directly affect E-Cad sorting in the endometrial epithelium which undergo EMT in response to embryonic stimuli.